Identification of Spindle and Kinetochore-Associated Family Genes as Therapeutic Targets and Prognostic Biomarkers in Pancreas Ductal Adenocarcinoma Microenvironment - Liu, Yi; Jin, Zong-rui; Huang, Xing; Che, Ye-cheng; Liu, Qin (Frontiers in Oncology, 2020)
Aim: The role of spindle and kinetochore associated (SKA) genes in tumourigenesis and cancer progression has been widely studied. But so far, the oncogenic involvement of SKA family genes in pancreatic cancer, and their prognostic potential remains unknown. Methods: Here, we carried out a meta-analysis of the differential expression of SKA genes in normal and tumour tissue. Univariate and multivariate survival analyses were done to evaluate the correlation between SKA family genes expression and pancreas ductal adenocarcinoma (PDAC) prognosis. Joint-effect and stratified survival analysis as well as nomogram analysis were used to estimate the prognostic value of genes. The underlying regulatory and biological mechanisms were identified by Gene Set Enrichment Analysis. Interaction between SKA prognosis-related genes and immune cell infiltration was assessed using Tumour Immune Estimation Resource tool (TIMER). Results: We find that SKA1-3 are highly expressed in PDAC tissues relative to non-cancer tissues. Survival analysis revealed that high expression of SKA1 and SKA3 independently indicate poor prognosis but only SKA3 was associated with relapse-free survival. The prognostic value of SKA1 and SKA3 were further confirmed by the nomogram, joint‐effect and stratified survival analysis. Analysis of underlying mechanisms reveal that these genes influence cancer-related signaling pathways, kinases, miRNA and E2F family genes. Notably, prognosis-related genes are inversely correlate with several immune cells infiltrating levels. Conclusion: We find that SKA1 and SKA3 expression correlates with prognosis and immune cells infiltration in PDAC, highlighting their potential as pancreatic cancer prognostic biomarkers.